(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
PT Asuransi Buana Independent is a general insurance company that has obtained a Financial Services Authority (OJK) business license. The purpose of this research is to determine the influence of interpersonal relationships, work environment and compensation on employee morale at PT. Buana Independent Insurance. The time of the research is February 2023. The researcher took the population in this study as 119 employees who work in the company. To determine the sample using the Slovin formula, the tolerance level is 5%, where the total results of the calculations carried out were obtained as many as 92 research samples. The research results found that interpersonal relationships had a positive and significant effect on the work spirit of PT employees. Buana Independent Insurance. The work environment has a positive and significant effect on the work spirit of PT employees. Buana Independent Insurance. Compensation has a positive and significant effect on PT employee morale. Buana Independent Insurance. Simultaneously Interpersonal Relations, Work Environment and Compensation have a significant influence on the Work Morale of PT employees. Buana Independent Insurance.